Manajemen Pembelajaran Pendidikan Agama Islam untuk Penguatan Karakter Agama dan Moral - Nuraeni, Siti; Sukandar, Ahmad; Helmawati, Helmawati (CV. Media Publikasi Profesional, 2021)
The study is set against the backdrop of a phenomenon that occurs in society today, regarding the numberof attitudes or behavior and moral decline that is often shown by student, which worries all parties, including school institusions. As an educational institution, school make it possible to create learning activities related to character to strengthening in children, because education in school is formulated in an orderly manner compared to other education, so that schools have an important and strategic role in realizing a generation of people who have good character. To achieve these expectations, scholls should be able to design, plan, implement, supervise, and assessment the strengthening of reeligius and moral characters through learning Islamic Religious Education. TKQ Al Amin and TKQ Al Musyawaroh are schools that carry out management activities in PAI learning to strengthen the religious and moral character of student. This study aims to determine the planning, implementation, and learning assessment of Islamic education learning to strengthen religious and moral characters. The results of this study can contribute and broaden insights to the school principal, teachers of TKQ, chief organization of TKQ , and parents of students about management of Islamic education learning to strengthen religious and moral character. The study used qualitative descriptive methods, data collection techniques conducted with interviews, observation, and documentary studies. This study uses the teory of management functions.s Research shows that learning management activities at TKQ Al Amin and TKQ Al Musyawaroh have appeared to be developing quite well, visible from: 1) the availability of learning planning activities, such as: organizing the annual vision, mission, and learning program, semester program, weekly and daily activities plan. 2) the implementation of learning is held to religious and moral character through regular and spontaneous imitation and habituation, through the learning stages i.e , early learning activities, core activities, breaks, and closing activities. 3) learning assessment covers all aspects of child development which is implemented by observation, checklists, oral and non-verbal tests. 4) inhibiting factors and supporting factors provide the motivation for more optimal learning programs.